A DATA ANALYSIS OF THE IMPACT OF NATURAL DISASTER USING K-MEANS CLUSTERING ALGORITHM - Prihandoko Prihandoko; Bertalya Bertalya (Jurnal Ilmiah Kursor, 2016)
Indonesia is one of the country with a lot of natural disasters occurred every year. The victims of natural disasters, are quite high in terms of the number of deaths, missing people, injuries, sufferings and the number of refugees. Unfortunately, the number of victims is growing from year to year in the last ten years. Thus, based on this condition, this research is carried out in order to analyze the data of the natural disasters and their victims for the last five years. The analysis is intended to know what is the main cause of natural disaster. The series of data about the natural disaster and the weather condition is collected from the government office website. The analysis was carried out by implementing clustering technique to the data, by using k-means algorithm, after data preprocessing completed. The result of the research shows that the weather condition is not the main cause of the occurrence of natural disaster, but the geographical condition is the main trigger of the problem. In addition, this research also found that the data published by the government need to be updated regularly.